The Southern Middle Class in the Long Nineteenth Century - Wells, Jonathan Daniel, 1969-; Green, Jennifer R., 1970- (Book collections on Project MUSE., 2011)
In the past few years historians have begun to offer exciting accounts of the emergence of an influential and vibrant southern middle class during the nineteenth century. Wells and GreenAEs book provides a series of provocative essays reflecting innovative, original research on professional and commercial interests in a region often seen as composed of just two classesùplanters and slaves. Rather, the active middle class, made up of professional and commercial men and women devoted to cultural and economic modernization of the region, worked in tandem with its northern counterpart, and independ.